2009
DOI: 10.1016/j.wombi.2009.01.004
|View full text |Cite
|
Sign up to set email alerts
|

‘It looks good on paper’: Transitions of care between midwives and child and family health nurses in New South Wales

Abstract: A more coordinated and systematised approach needs to be developed. Collaboration and communication between midwives and child and family health nurses is essential if the needs of families are to be addressed during this transition period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 19 publications
1
48
0
1
Order By: Relevance
“…In one discursive paper, studies with and without consideration of the midwives' perspective were included, which led to the exclusion of the article. However, one of the studies included met the inclusion criteria and had been incorporated in the results previously (Homer et al, 2009). Seven studies were found to have irrelevant topics and were, therefore, excluded.…”
Section: Full-text Screeningmentioning
confidence: 99%
See 4 more Smart Citations
“…In one discursive paper, studies with and without consideration of the midwives' perspective were included, which led to the exclusion of the article. However, one of the studies included met the inclusion criteria and had been incorporated in the results previously (Homer et al, 2009). Seven studies were found to have irrelevant topics and were, therefore, excluded.…”
Section: Full-text Screeningmentioning
confidence: 99%
“…Six studies focus on the collaboration between midwives and nurses at the point where care progresses between midwifery services and child or family health care (Barimani & Hylander, 2008;Barimani & Hylander, 2012;Homer et al, 2009;Psaila, Kruske, Fowler, Homer, & Schmied, 2014;Psaila et al, 2015). This shows a particular characteristic of the care systems in Sweden and Australia.…”
Section: Cooperation Contextsmentioning
confidence: 99%
See 3 more Smart Citations